A Longitudinal Study of Stress in New Nurses in their First Year of Employment. (21st November 2022) - Fang, Yan; Yang, Jingping; Zhang, Mengling; Song, Jihong; Lin, Rongjin
Abstract : Objective . This study aimed to analyze changes in occupational stress in new nurses during the first year of employment. Methods . A prospective longitudinal study was conducted from 2020 to 2021 using one questionnaire four times on 127 newly employed nurses in a tertiary general teaching hospital in the province of Fujian. Results . The results showed that new nurses had moderate to high levels of stress in all four stages, with the highest stress level at 4 and 8 months of employment and the lowest stress level at 12 months; the differences in stress scores at different time points were statistically significant (p < 0.05 ). The trends in each stressor dimension varied across different periods. The highest scores were for pressure caused by "time allocation and workload, " which peaked in month 8. The same trend was observed for stress from "patient care" and "work environment and equipment." "Management and interpersonal relationships" scored the highest overall stress score at the start of employment before declining. The lowest stress score was from "work environment and equipment" at the start of employment, and the lowest was from "management and interpersonal relationships" from month 4 onward. Conclusion . New nurses had higher overall occupational stress during their first year of employment under different stressors. Therefore, nursing managers should actively focus on stress factors of new nurses and provide targeted interventions to help them during their training period.